Analisis Penggunaan Sarkasme pada Demonstrasi Indonesia Gelap 21 Februari 2025: Semiotika Ferdinand De Saussure - Yani, April; Nola Syahfira, Krista; Siahaan, Yesika; Winkasari, Tiara; Harahap, Muharrina (eScience Humanity Journal, 2025)
This study analyzes the use of sarcasm in the "Dark Indonesia" demonstration on February 21, 2025 using Ferdinand de Saussure's semiotic approach. Sarcasm is used as a communication tool to convey criticism of government policies through speeches, protest banners, and social media. This study is qualitative descriptive with data obtained from the TikTok platform. The results of the analysis show that sarcasm functions as an effective form of expression of social criticism, reflecting public dissatisfaction with government policies. Using the concept of signifiers and signifieds, this study reveals the meaning behind sarcastic speech and its impact on political discourse in Indonesia. This study contributes to linguistic studies and understanding of the role of language in socio-political dynamics.